Development of a modified Cambridge Multimorbidity Score for use with SNOMED CT: an observational English primary care sentinel network study - Tsang, RSM; Joy, M; Whitaker, H; Sheppard, JP; Williams, J; Sherlock, J; Mayor, N; Meza-Torres, B; Button, E; Williams, AJ; Kar, D; Delanerolle, G; et al. (Royal College of General Practitioners, 2023)
Background People with multiple health conditions are more likely to have poorer health outcomes and greater care and service needs; a reliable measure of multimorbidity would inform management strategies and resource allocation.